Analysis of the Effect of Poverty Levels, APBD Allocation for Health, and Per Capita GRDP on the Human Development Index in West Nusa Tenggara Province from 2014 to 2023 - Tia Hariani; Emi Salmah; Gusti Ayu Arini (Westscience Press, 2026)
This study aims to analyze the influence of poverty levels, allocation of the Regional Revenue and Expenditure Budget (APBD) for the health sector, and Gross Regional Domestic Product (GRDP) per capita on the Human Development Index (HDI) in West Nusa Tenggara Province (NTB) during the period 2014 to 2023. The research approach uses a quantitative method with multiple linear regression analysis based on panel data. The results show that partially the variables of poverty levels and GRDP per capita do not significantly influence the HDI. However, the allocation of the APBD for health has a positive and significant influence on the increase in the HDI in NTB, which indicates that the increase in the budget in the health sector contributes significantly to improving the quality of life of the community. Simultaneously, these three variables contribute to changes in the HDI, although the influence is not significant overall. This study recommends strengthening more integrated human development policies, particularly in the allocation of the health budget which has a direct impact on increasing life expectancy and the quality of human resources.